Phytochemical Characterization and In Vitro Antibacterial Activity of Turbinaria Conoides Against Clinical Pathogens - S. Sivanantham; M. Kalaivani; S. Harshini; E. Manimozhi; E. Nivetha; A. Poorvisha; S. Rathika; M. Ragavi (International Journal of Science, Strategic Management and Technology, 2026)
Marine macroalgae are recognized as valuable sources of structurally diverse bioactive metabolites with potential pharmaceutical and biotechnological applications. The present study investigated the phytochemical composition and in vitro antibacterial activity of the brown macroalga Turbinaria conoides collected from the Pamban coastal region of Tamil Nadu, India. The collected biomass was thoroughly washed, shade-dried, powdered, and subjected to aqueous and acetone extraction. Aqueous extraction was performed by thermal treatment, while acetone extraction was carried out using a Soxhlet apparatus. The resulting extracts were evaluated for extraction yield and qualitatively screened for major phytochemical classes. Their antibacterial activity was subsequently assessed against Escherichia coli using the agar well diffusion method. The acetone and aqueous extraction procedures yielded 2.1% and 5.2%, respectively. The acetone extract showed positive reactions for phenols, tannins, flavonoids, glycosides, terpenoids, alkaloids, and phytosterols, whereas saponins and steroids were not detected. In contrast, the aqueous extract contained tannins, saponins, alkaloids, and proteins, while phenols, flavonoids, glycosides, terpenoids, phytosterols, and steroids were not detected. Both extracts exhibited inhibitory activity against E. coli, indicating measurable antibacterial potential. The observed differences in phytochemical profiles between the extracts demonstrate the influence of extraction solvent on the recovery of bioactive constituents from T. conoides. Overall, the findings provide preliminary evidence supporting T. conoides as a potential source of naturally derived antibacterial metabolites. Further investigations involving quantitative phytochemical analysis, chromatographic and spectroscopic characterization, minimum inhibitory concentration determination, broader pathogen screening, and mechanistic studies are required to identify the compounds responsible for the observed antibacterial activity and establish their biological significance.